Potential syntrophic relationship between coral-associated Prosthecochloris and its companion sulfate-reducing bacterium unveiled by genomic analysis. Issue 5 (5th May 2021) - Chen, Yu-Hsiang; Yang, Shan-Hua; Tandon, Kshitij; Lu, Chih-Ying; Chen, Hsing-Ju; Shih, Chao-Jen; Tang, Sen-Lin
Abstract : Endolithic microbial symbionts in the coral skeleton may play a pivotal role in maintaining coral health. However, compared to aerobic micro-organisms, research on the roles of endolithic anaerobic micro-organisms and microbe–microbe interactions in the coral skeleton are still in their infancy. In our previous study, we showed that a group of coral-associated Prosthecochloris (CAP), a genus of anaerobic green sulphur bacteria, was dominant in the skeleton of the coral Isopora palifera . Though CAP is diverse, the 16S rRNA phylogeny presents it as a distinct clade separate from other free-living Prosthecochloris . In this study, we build on previous research and further characterize the genomic and metabolic traits of CAP by recovering two new high-quality CAP genomes – Candidatus Prosthecochloris isoporae and Candidatus Prosthecochloris sp. N1 – from the coral I. palifera endolithic cultures. Genomic analysis revealed that these two CAP genomes have high genomic similarities compared with other Prosthecochloris and harbour several CAP-unique genes. Interestingly, different CAP species harbour various pigment synthesis and sulphur metabolism genes, indicating that individual CAPs can adapt to a diversity of coral microenvironments. A novel high-quality genome of sulfate-reducing bacterium (SRB)– Candidatus Halodesulfovibrio lyudaonia – was also recovered from the same culture. The fact that CAP and various SRB co-exist in coral endolithic cultures and coral skeleton highlights the importance of SRB in the coral endolithic community. Based on functional genomic analysis of Ca . P. sp. N1, Ca . P. isoporae and Ca . H. lyudaonia, we also propose a syntrophic relationship between the SRB and CAP in the coral skeleton.